2018
DOI: 10.20892/j.issn.2095-3941.2018.0012
|View full text |Cite
|
Sign up to set email alerts
|

Enterolactone modulates the ERK/NF-κB/Snail signaling pathway in triple-negative breast cancer cell line MDA-MB-231 to revert the TGF-β-induced epithelial–mesenchymal transition

Abstract: Objective:Triple-negative breast cancer (TNBC) is highly metastatic, and there is an urgent unmet need to develop novel therapeutic strategies leading to the new drug discoveries against metastasis. The transforming growth factor-β (TGF-β) is known to promote the invasive and migratory potential of breast cancer cells through induction of epithelial–mesenchymal transition (EMT) via the ERK/NF-κB/Snail signaling pathway, leading to breast cancer metastasis. Targeting this pathway to revert the EMT would be an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…TGF-β, a major inducer of EMT, is overexpressed in breast cancer, and is associated with malignant progression and poor prognosis (16). Adding TGF-β to epithelial cells in culture induces EMT in vitro (17,18). TGF-β induces EMT through a Smad-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β, a major inducer of EMT, is overexpressed in breast cancer, and is associated with malignant progression and poor prognosis (16). Adding TGF-β to epithelial cells in culture induces EMT in vitro (17,18). TGF-β induces EMT through a Smad-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ASX inhibits migration in the TNBC and ER + breast cancer cells examined in these experiments. The MDA-MB-231 TNBC line is highly metastatic [ 32 ] but its migratory capacity is attenuated by ASX treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB signaling pathway is closely related to tumorigenesis, invasion, and metastasis. [24][25][26] Yang et al found that p65-regulated EMT induced by the low-dose irradiation of cervical cancer cell lines promotes invasiveness and metastasis. 27 Interestingly, studies have reported that CXCL1 promotes breast cancer metastasis via NF-κB.…”
Section: Discussionmentioning
confidence: 99%